Solving group decision-making problems in manufacturing systems by an uncertain compromise ranking method. (2018) - Mousavi, S. Meysam; Foroozesh, N.; Gitinavard, H.; Vahdani, Behnam
The purpose of this paper is to introduce a new modified compromise ranking method (VIKOR), known as sorting the possible alternatives and determining the compromise solution under interval-valued hesitant fuzzy sets (IVHFSs) for solving group decision-making problems in manufacturing systems. By using numerical measure and crisp data, the decision making is complex in real-life situations because the decision makers (DMs)' judgments are usually hesitant and vague. A more applicable and realistic approach based on interval-valued hesitant fuzzy elements (variables) is presented and defined as the inputs to the presented VIKOR method. The proposed interval-valued hesitant fuzzy modified VIKOR (IVHF-MVIKOR) method utilises the membership degrees to demonstrate the degrees of satisfiability for each possible alternative according to selected criteria for the manufacturing assessments. Then, a new index for relative importance of the DMs is introduced with the extended fuzzy sets. Also, some operations in the proposed IVHF-MVIKOR method are developed for manufacturing decision problems. Then, new indexes are presented with interval-valued hesitant fuzzy hamming distance measure for the purpose of rankings. Finally, by presenting a practical example in flexible manufacturing systems, the performance of IVHF-MVIKOR method is evaluated and compared with two well-known methods under interval-valued hesitant fuzzy information.